Wise Feedback as a Timely Intervention for At-Risk Students Transitioning Into High School. Issue 3 (1st September 2018) - Thayer, Andrew J.; Cook, Clayton R.; Fiat, Aria E.; Bartlett-Chase, Meghanne N.; Kember, Jessie M.
Abstract: A promising development in school-based prevention and intervention science is the use of applied social–psychological concepts to improve students' experiences and outcomes in school. Mounting evidence from rigorous studies supports the efficacy of theoretically informed interventions grounded in social psychology, including growth mindset and values affirmation. One of particular utility for educators and school psychologists is wise feedback, which is a relational technique for providing skillful, constructive feedback. The overarching purpose of this study was to further explore the potential efficacy of wise feedback as a targeted intervention for students exhibiting social problem behaviors resulting in negative outcomes. Wise feedback was implemented using a multiple-baseline design with six students exhibiting signs of dropout (i.e., lack of trust and sense of belonging in a school) in ninth grade. Visual and statistical analysis indicated improvement in the students' sense of belonging and trust in their schools. Implications, limitations, and future directions are discussed.